TRANSPARANSI INFORMASI PUBLIK DALAM PENYELENGGARAAN PEMILU LEGISLATIF - ', Ismail (Jurnal Ilmu Administrasi Negara, 2017)
Abstract: Transparency of Public Information in the Implementation of the legislative electionsin 2014. Objective was to determine the type of data in the category of public informationtransparency and barriers to implementation of public information transparency in the implementationof the 2014 legislative elections in the province of Riau. As for the key informants in thisstudy is the Chairman of the Election Commission along with the ranks of Riau province Organickesektariatan Commission. Susulannya informant is using snowball sampling technique. Thetechnique of collecting data using interviews and documents. Analysis of data using an interactivemodel. The results showed that overall the 2014 legislative elections run in accordance withthe mandate of the Act. Irregularities and obstacles that occur in the form of issue of the capabilitiesand quality of human resources from the ranks of the organizers who have not been balancedwith the workload.